Patients With IBD Receiving Methotrexate Are at Higher Risk of Liver Injury Compared With Patients With Non-IBD Diseases: A Meta-Analysis and Systematic Review - Wang, Yang; Li, Yimin; Liu, Yun; Zhang, Yifan; Ke, Ziliang; Zhang, Yu; Liu, Yulan (Frontiers in Medicine, 2021)
Background: Methotrexate (MTX) is well-known in treating inflammatory bowel disease (IBD), rheumatoid arthritis (RA), psoriasis (Ps) and psoriatic arthritis (PsA). Several reports have indicated a higher incidence of MTX-related liver adverse events in patients with IBD. We aim to investigate the risk of liver injury in patients with IBD and those with non-IBD diseases treated with MTX. Methods: We searched PubMed for articles that reported liver adverse events in patients with IBD, RA and Ps/PsA receiving MTX therapy. Additional articles were obtained by screening the references of recent meta-analysis and reviews. Raw data from included articles were pooled to calculate the cumulative incidence of total liver injury (TLI), MTX discontinuation (MTX-D) and liver fibrosis (LF). RR (relative risk) was calculated to compare the difference between patients with IBD and those with non-IBD diseases. Results: A total of 326 articles with 128,876 patients were included. Patients with IBD had higher incidence of TLI (11.2% versus 9.2%; relative risk (RR) = 1.22; P = 0.224) and MTX-D (2.6% versus 1.8%; RR, 1.48; P = 0.089) than patients with non-IBD diseases. Due to the publication bias, trim-and-fill was performed. Afterwards, patients with IBD showed significantly higher risk of TLI (11.2% versus 3%; RR = 3.76; P < 0.001), MTX-D (3.3% versus 0.7%; RR = 5; P < 0.001) and LF (3.1% versus 0.1%; RR = 38.62; P = 0.001) compared with patients with non-IBD diseases. Conclusion: IBD is associated with a higher risk of MTX-related liver injury. The mechanism of MTX-induced hepatotoxicity might be different in IBD and non-IBD diseases, and needs to be verified in future research.